Heavy metal(loid)s in farmland soils on the Karst Plateau, Southwest China: An integrated analysis of geochemical baselines, source apportionment, and associated health risk. (11th April 2022) - Han, Jialiang; Liang, Longchao; Zhu, Yaru; Xu, Xiaohang; Wang, Le; Shang, Lihai; Wu, Pan; Wu, Qixin; Qian, Xiaoli; Qiu, Guangle; Feng, Xinbin
Abstract: The Karst Plateau is characterized by elevated heavy metals (HM), the farmland soils in the Karst Plateau area is especially vulnerable to HM pollution. To cope with soil HM pollution and conduct precaution in Karst Plateau, the key bottleneck is to understand the pollution levels, sources, and priority‐control of HM. Hence, geochemical baselines of HM in farmland soils were established to accurately evaluate the pollution characteristics. Pollution sources were identified with multivariate statistics, geostatistical methods, and receptor models. Priority‐control of HM were distinguished via health assessments with a Monte Carlo simulation. A remarkable accumulation of Pb, Sb, Zn, As, and Cd was observed. Hotspots of As, Cd, Pb, Sb, and Zn clustered in the southwestern region of Hezhang. Pb–Zn related activities, cement product activities, coal mining, and coal combustion were dominant sources. Both noncarcinogenic risk and carcinogenic risk followed the order: children>adult females>adult males. As, Cd, and Pb were found to be priority contaminants in farmland soils in Hezhang.